2016
DOI: 10.1038/ijo.2016.131
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 and SIRT7 expression in adipose tissues of obese and normal-weight individuals is regulated by microRNAs but not by methylation status

Abstract: We observed obesity-associated downregulation of SIRT1 and upregulation of SIRT7 mRNA levels that were not associated with the methylation status of their promoters. We found a negative correlation between mRNA levels of SIRT1 in VAT of obese individuals and SIRT7 in VAT of the normal-weight subjects and expression of the relevant miRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 57 publications
5
59
1
Order By: Relevance
“…A recent study revealed that reduced Sirt1 mRNA level in adipose tissue of obese patients was correlated negatively with the level of miR-22 [33]. Interestingly, activation of Sirt1 induces the browning of white adipose tissue and promotes resistance to obesity [34], suggesting that factors that regulate Sirt1 might attenuate the metabolic disorders associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that reduced Sirt1 mRNA level in adipose tissue of obese patients was correlated negatively with the level of miR-22 [33]. Interestingly, activation of Sirt1 induces the browning of white adipose tissue and promotes resistance to obesity [34], suggesting that factors that regulate Sirt1 might attenuate the metabolic disorders associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have similarly shown that SIRT1 is expressed in both subcutaneous and visceral WAT and reduced by obesity [43], [69], [106], [107], [108], [109], [110]. The expressions of SIRT2, SIRT3 and SIRT5 were reported to be either reduced [43], [69], [102], or unaffected in obese subcutaneous WAT [108]. For SIRT7 results between different studies have also been varied: Rappou and colleagues [69] found decreased expression in obese subcutaneous WAT, whereas no expression difference [43] or increased expression [108] has also been reported.…”
Section: Sirts and Parps In Adipose Tissue Function In Basal And Obesmentioning
confidence: 99%
“…In contrast, caloric restriction increases Sirt1 and Sirt2 but reduces Sirt4 mRNA and protein level in WAT [85], [103], [104], [105]. Human studies have similarly shown that SIRT1 is expressed in both subcutaneous and visceral WAT and reduced by obesity [43], [69], [106], [107], [108], [109], [110]. The expressions of SIRT2, SIRT3 and SIRT5 were reported to be either reduced [43], [69], [102], or unaffected in obese subcutaneous WAT [108].…”
Section: Sirts and Parps In Adipose Tissue Function In Basal And Obesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, miR-133 targets this pathway at two different points [99]. In humans, Kurylowicz et al observed that the downregulation of SIRT1 negatively correlated with the expression of miR-22-3p in obese individuals and the upregulation of SIRT7 negatively correlated with miR-125a-5p levels in slim individuals [141]. Another study in humans showed the importance of the regulation of miR-199 as a modulator of SIRT1 and as a biomarker of atrial fibrillation after coronary artery bypass graft surgery [142].…”
Section: Miragings: What and Which Are They? How Can They Be Modulmentioning
confidence: 99%